Social innovation: combining profits and progress - Sondos Gamaleldin Sobhy Abdelgawad (Edward Elgar Publishing, 2018)
A growing number of new and established organizations are addressing social ills through innovative and profitable organization. In that regard, we seek to understand how a deeper understanding of social innovation can be achieved by a more sophisticated discussion of organizational form. In this chapter we ask, 'Which organizational designs and practices can meet both financial and social objectives?' and 'How can organizations use those practices to profitably address social ills such as poverty, social inequity, climate change, and educational failure?' This chapter draws on novel data, practitioners' experiences, and dozens of interviews to highlight the organizational design and innovation behavior that further the profitable pursuit of social innovation. We focus on benefit corporations or B-corporations as an organizational design that simultaneously delivers business and social impact. We then identify and analyze behaviors within established companies that support social innovation. B-corporations currently exist in 50 countries. They are certified and have their social and environmental impact formally tracked and publicly reported by B-Lab. B-Lab is a non-profit organization that serves and inspires the global movement of 'B-corporations' with the aim of building a global community, promoting mission alignment, and helping social innovators 'measure what matters in the business'. B-Lab's main instrument is the B-Lab Impact Assessment, which determines the outcome of B-Lab certification. Legal benefit corporations (currently only in the US) may choose to be certified as 'B-corporations' as well, though there is no strict requirement to do so. Here, we report on stylized findings from the data.